2019
DOI: 10.1177/1545968319883880
|View full text |Cite
|
Sign up to set email alerts
|

Hand Motor Actions of Children With Cerebral Palsy Are Associated With Abnormal Sensorimotor Cortical Oscillations

Abstract: Background. The neuroimaging literature on cerebral palsy (CP) has predominantly focused on identifying the structural aberrations (eg, fiber track integrity), with very few studies examining neural activity within the key networks that serve the production of hand movements. Objective. We aimed to start to fill this knowledge gap by using magnetoencephalographic brain imaging to quantify the temporal dynamics of the sensorimotor oscillations during a hand motor action. Methods: Children with CP (n = 12; MACS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 66 publications
4
14
0
Order By: Relevance
“…Our results also revealed that the PMBR was weaker for the adults with CP. This result is well aligned with our prior work, which has shown that the PMBR is weaker in youth with CP compared with controls when performing the same Eriksen anker task 50 . The PMBR is thought to re ect afferent sensory feedback upon completion of the motor action, 31,32 although other possible functions cannot be ruled out [33][34][35][36][37] .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results also revealed that the PMBR was weaker for the adults with CP. This result is well aligned with our prior work, which has shown that the PMBR is weaker in youth with CP compared with controls when performing the same Eriksen anker task 50 . The PMBR is thought to re ect afferent sensory feedback upon completion of the motor action, 31,32 although other possible functions cannot be ruled out [33][34][35][36][37] .…”
Section: Discussionsupporting
confidence: 92%
“…In fact, only one study to date has quanti ed the strength of the PMBR and gamma ERS during upper extremity movements, and this study indicated weaker responses in youth with CP during performance of an arrow-based version of the Eriksen anker task 50 . Although these investigations have advanced our understanding of the impact of CP on sensorimotor cortical oscillations, we still have major knowledge gaps in our understanding of these cortical oscillations, especially in adults with CP, despite the overwhelming clinical impression that there is a decline in hand motor function throughout adulthood.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…In addition, Piitulainen et al (2018) suggested the impaired excitation-inhibition balance and Riquelme and Montoya (2010) enhanced excitability in the somatosensory cortices in CP. Moreover, post-movement beta rebound amplitude in the SM1 cortex correlates positively with higher GABA levels in the SM1 cortex ( Gaetz et al, 2011 , Cheng et al, 2017 ), and is weaker in individuals with CP participants ( Hoffman et al, 2019 ) and especially in their more affected side ( Pihko et al, 2014 ). Animal models of CP show hindered GABAergic inhibition and increased responsiveness of the SI cortex ( Coq et al, 2008 ) and post-mortem studies of neonates report loss of GABAergic neurons associated with the perinatal brain injury ( Robinson et al, 2006 , Stolp et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%